War on Two Fronts: The Fight against Parasites in Korea and Vietnam. Issue 3 (12th June 2017) - Harrison, Mark; Yim, Sung Vin
Abstract : The Vietnam War has long been regarded as pivotal in the history of the Republic of Korea, although its involvement in this conflict remains controversial. While most scholarship has focused on the political and economic ramifications of the war – and allegations of brutality by Korean troops – few scholars have considered the impact of the conflict upon medicine and public health. This article argues that the war had a transformative impact on medical careers and public health in Korea, and that this can be most clearly seen in efforts to control parasitic diseases. These diseases were a major drain on military manpower and a matter of growing concern domestically. The deployment to Vietnam boosted research into parasitic diseases of all kinds and accelerated the domestic campaign to control malaria and intestinal parasites. It also had a formative impact upon the development of overseas aid.